False papers and family fictions: household responses to 'gift children' born to Indonesian women during transnational migration. Issue 6 (2nd October 2016) - Butt, Leslie; Ball, Jessica; Beazley, Harriot
Abstract: When parents pursue transnational labour migration, challenges arise around ensuring the social belonging of children, especially 'gift children' who are conceived or born abroad as a result of out-of-wedlock relationships or sexual assault. Families we interviewed in Lombok, Indonesia, displayed complex social ingenuity to ensure the gift child's social belonging. Caregivers described how they address discrimination by manipulating and falsifying family histories in identity documents, including census forms and birth registration. These family strategies drive home the local role of identity documents as a tool to enhance belonging rather than as proof of legal identity. We spotlight the time lag between birth and obtaining an official birth record as a crucial space in creating 'citizenship from below' in communities with high out-migration and low birth registration rates.